2015
DOI: 10.1139/cjm-2014-0615
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of fatty acid profile and formation of biofilm inGeobacillus gargensisexposed to variable abiotic stress

Abstract: Understanding bacterial fatty acid (FA) profile has a great taxonomic significance as well as clinical importance for diagnosis issues. Both the composition and nature of membrane FAs change under different nutritional, biotic and (or) abiotic stresses, and environmental stress. Bacteria produce both odd-carbon as well as branched-chain fatty acids (BCFAs). This study was designed to examine the effect of abiotic pressure, including salinity, temperature, pH, and oxinic stress on the growth, development, and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…We hypothesize that bacterial BCFAs are essential for the formation of the tongue coating in IOH. Recently, Al-Beloshei et al (2015) showed that the bacterial BCFA levels increase during biofilm formation at neutral and alkaline pHs [32]. This observation is consistent with our current findings.…”
Section: Discussionsupporting
confidence: 93%
“…We hypothesize that bacterial BCFAs are essential for the formation of the tongue coating in IOH. Recently, Al-Beloshei et al (2015) showed that the bacterial BCFA levels increase during biofilm formation at neutral and alkaline pHs [32]. This observation is consistent with our current findings.…”
Section: Discussionsupporting
confidence: 93%
“…More specifically, Bacillus subtilis can colonize L. longipalpis larvae gut under laboratory conditions (Heerman et al , 2015 ). Curiously the Geobacillus genus, that can form biofilms on food industry surfaces (Seale et al , 2012 ; Al-Beloshei et al , 2015 ) is present in the L. longipalpis studied samples and has been rarely studied in insects. The sand fly bacterial diversity and distribution indicates that although laboratory feeding systems can interfere in the L. longipalpis natural microbial diversity, some bacteria species can persist through the adult fly feeding and environmental differences (field and laboratory conditions).…”
Section: Sand Fly Microbiotamentioning
confidence: 99%
“…Increases in environmental pH correlate with increases in branched and unsaturated fatty acid content [78][79][80] , and acidic stress leads to an altered fatty acid profile 78,79 , suggesting that extracellular pH may influence fatty acid metabolism. To address how alkaline stress might increase demand for biotin, fatty acid abundance was measured in M. abscessus grown in tissue culture medium either at pH 7.8 or pH 6.8.…”
Section: Alkaline Ph Imposes Demand For Biotin and Alters Fatty Acid ...mentioning
confidence: 99%